(3EOGQI GdJShjb (B/s - (3GdYdGb, HTjQs; (3bMWGf, GdYHOdjs ((3YeGf(B: s (3OGQ RgQGf ddfTQ hGdJhRjY(B, s, 2006)
(3EOGQI GdfTGW GdJShbj,YedjI EOGQI GdJShjb,JNWjW GdfTGW GdJShjbj,JfXje GdfTGW GdJShjbj,JfSjb GdfTGW GdJShjbj ,JhLjg GdfTGW GdJShjbj ,GdQbGHI Ydi GdfTGW GdJShjbj ,GSJQGJjLjGJ GdeRjL GdJShjbj,GJNGP GdbQGQGJ GdJShjbjI ,GdbjGS hGdJfHD HGdWdH,fXe GdeYdheGJ hHMhK GdJShjb, GdJShjb GdOhdjs
(3HHdjhZQGajG(B:(3U(B.401-404s
Keywords: (3EOGQI GdJShjbs